Breeding and genetic peculiarities of modern spring barley varieties for grain number per main ear - С. П. Васильківський; В. М. Гудзенко; О. А. Демидов; О. Б. Барбан; С. С. Коляденко; І. В. Смульська (Plant Varieties Studying and Protection)
Purpose. To reveal breeding and genetic peculiarities of modern spring barley varieties for the “number of grains per main ear” trait and identify genetic sources of increased combining ability for involving in hybridization.